Responses of laying performance, eggshell quality, calcium, and phosphorus metabolism to feeding patterns and dietary available phosphorus levels in aged laying hens - Dan Shao; Liangji Liu; Haibing Tong (Poultry Science)
This study aimed to determine the effects of feeding patterns and dietary available phosphorus levels on laying performance, eggshell quality, calcium, and phosphorus metabolism in aged laying hens. The experiment followed a 3 × 2 factorial arrangement of three feeding patterns (feeding twice a day, 1/2 daily feeding at 8:00, and 1/2 daily feeding at 14:00; disequilibrium feeding twice a day, 1/3 daily feeding at 8:00, and 2/3 daily feeding at 14:00; feeding thrice a day, 1/3 daily feeding at 8:00, 1/3 daily feeding at 14:00, and 1/3 daily feeding at 18:00) and two available phosphorus levels (0.32 %, 0.27 %) was carried out with a total of 528 Hy-Line Brown laying hens aged 62–74 weeks. Each group had 8 replicates of 11 hens. The results revealed that feeding patterns and phosphorus levels significantly interacted with egg production ratios, soft shell and broken egg ratios in weeks 9–12 (P < 0.05). Feeding thrice a day and disequilibrium feeding twice a day significantly improved the equatorial and average eggshell thickness (P < 0.05), and had a trend of increasing eggshell strength at week 12 (P = 0.068). They also significantly increased the effective layer thickness and the calcified layer thickness of the eggshell (P < 0.05). Additionally, feeding thrice a day significantly increased serum calcium content compared with feeding twice a day (P < 0.05), and feeding thrice a day significantly increased the calcium content of the eggshell, mRNA expression level of CaBP-D28k in the uterine compared with the other two feeding patterns (P < 0.05). While disequilibrium feeding twice a day resulted in higher phosphorus content in the excreta compared with the other two feeding patterns (P < 0.05). These results indicated that feeding hens thrice a day with 0.27 % dietary available phosphorus level might improve in laying performance and eggshell quality of aged laying hens.